The gold-money rift : a classical theory of international liquidity - Brahmananda, P. R.; Bagal, K. L.; Iyengar, Sampath S.; Nathan, Dev. (New York : Humanities Press, 1969)
This book outlines a framework of modernized classical thinking on the international monetary system. This was a departure of the neo-classical and Keynesian thinking on issues in international liquidity settlement.
Includes index
Bibliography: p. 343-346.
usc 20/09/2017
Loans
Keywords: International liquidity